Políticas públicas de inclusão digital no litoral do Paraná - Angelin, Simone Ferreira Naves (2015)
The issue of Public Policies for Digital Inclusion in Brazil has drawn considerable attention, since the inclusion of the new Information and Communication Technologies (ICTs) is a reality in modern societies. It is currently under the responsibility of the Federal Government about 17 programs for digital inclusion. However, 42% of the population never accessed the Internet. Thus, the importance of this research lies in the possibility of producing reflections on the reality of public policies at regional and local levels. In this way, the survey aimed to analyze the implementation of public policies for existing digital inclusion in the Coast of Paraná, examining whether they include three dimensions: technical (providing access to computers, internet and computer basics), economic (access equipment and internet at subsidized prices) and cognitive (access to advanced courses through critical appropriation of technology). Therefore, the investigation began with bibliographic and documentary research, which allowed conducting dialogues with authors who discuss the following topics: public policy, digital inclusion, digital divide, information society, among others. After, work began mapping the existing programs for digital inclusion in Brazil, focusing on the Coast of Paraná. The mapping was carried out through the Map of Digital Inclusion (MID) of the Brazilian Institute for Information in Science and Technology (IBICT), the Secretary of the State of Paraná Strategic Affairs and the municipal governments of Paraná coast, enabling 33 recovery Digital Inclusion Points addresses (PIDs). Then it was undertaken field research. Documents were requested and analyzed regarding the PIDs and conducted participant observation and interviews with the local agents who work directly with digital inclusion programs. The survey revealed that digital inclusion programs in the Coast of Paraná are inclined greater attention to the technical dimension, not fully considering the economic and cognitive dimensions. It showed that the focus of policy in general is facing a specific type of equipment, the desktop computer, not thought on digital inclusion from other perspectives of ICT. Also revealed the existence of the shadow of a policy on the other, and they have been implemented in general in all locations, not making a study of the local specificities and needs.It was concluded that, in practice, the digital inclusion in Paraná coast is more focused on universalization of technology than the critical appropriation of it because most of the programs has fostered actions that only provide access to computers and the internet.